First Report of Alternaria Leaf Spot Caused by Alternaria tenuissima on Blueberry (Vaccinium corymbosum) in Western Australia - You, M P (Plant disease, 2014)
Blueberry (Vaccinium corymbosum) plants in a commercial plantation at Yanchep, Western Australia, in April and May 2013, showed a widespread leaf spotting condition. Leaf lesions were circular to irregular, light brown to gray, 1 to 5 mm in diameter, with distinct dark brownish red borders. A fungus was consistently recovered by plating surface-sterilized (1% NaOCl) sections of symptomatic leaf tissue onto water agar and sub-culturing onto potato dextrose agar (PDA). For conidial production, the fungus was grown on PDA under a 12-h/12-h dark/light photoperiod at 25°C. Fungal colonies had a dark olive color on both sides, with loose, cottony mycelium on the surface of cultures. Isolates showed morphological similarities to Alternaria tenuissima as described in other reports (1,3). Simple conidiophores ranged from 16.3 to 96.6 μm (mean 37.5 μm) and produced numerous conidia in long chains. Conidia ranged from 7.0 to 23.9 μm (mean 13.9 μm) in length and 3.9 to 7.5 μm (mean 5.7 μm) in width, contained two to five transverse septa, but only an occasional longitudinal septum was observed. Using a representative isolate, a PCR-based assay with the ITS1 and ITS4 primers was used to amplify from the 3' end of 16S rRNA, across ITS1, 5.8S rRNA, and ITS2 to the 5' end of the 26S rRNA (4). The DNA products were sequenced and BLAST analyses were used to compare sequences with those in GenBank (2). The sequence had ≥99% nucleotide identity with the corresponding sequence in GenBank (Accession No. KC568287) for A. tenuissima. The relevant information for a representative isolate has been lodged in GenBank (KF408355). A conidial suspension of 2.5 × 105 conidia ml-1 from a single-spore culture was spot inoculated onto 20 leaves, ranging from recently emerged to oldest, of 6-month-old V. corymbosum Nellie Kelly plants maintained at 18/13°C 12-h/12-h day/night and >90% relative humidity for 72 h post inoculation. Symptoms were evident by 18 days post inoculation and by 24 days consisted of pale brown lesions that were mostly 2.1 to 2.5 μm in diameter and with distinct dark brownish red borders. A. tenuissima, showing morphological characteristics identical to those described above, was re-isolated from lesions to fulfill Koch's postulates. No lesions occurred on an equivalent number of leaves of control plants inoculated with only deionized water. A culture of this representative isolate has been lodged in the Western Australian Culture Collection Herbarium maintained at the Department of Agriculture and Food Western Australia (Accession No. WAC13639). A. tenuissima has been reported across Australia on a range of other hosts. However, on V. corymbosum, the pathogen has only previously been recorded in Tasmania (2009). It may also have been the cause of a leaf spotting condition on V. corymbosum recorded in Victoria (1976) and New South Wales (1984), but mistakenly listed with A. alternata as the cause. To the best of our knowledge, this is the first record of A. tenuissima on V. corymbosum in Western Australia. With 10 to 30% of leaves showing disease symptoms widely spread on many V. corymbosum plants in the commercial plantation, this pathogen could potentially adversely affect the future production of blueberries in Western Australia. References: (1) F. L. Caruso and R. C. Ramsdell, eds. Compendium of Blueberry and Cranberry Diseases. American Phytopathological Society, St. Paul, MN, 1995. (2) J. C. Kang et al. Mycol. Res. 106:1151, 2002. (3) E. G. Simmons. Mycotaxon 70:325, 1999. (4) T. J. White et al. Pages 315-322 in: PCR Protocols: A Guide to Methods and Applications. Academic Press, San Diego, 1990